2016
DOI: 10.1021/acs.jpcb.6b07807
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Ultrafast Molecular Rotor, Auramine O, as a Fluorescent Amyloid Marker

Abstract: Recently, Auramine O (AuO) has been projected as a fluorescent fibril sensor, and it has been claimed that AuO has an advantage over the most extensively utilized fibril marker, Thioflavin-T (ThT), owing to the presence of an additional large red-shifted emission band for AuO, which was observed exclusively for AuO in the presence of fibrillar media and not in protein or buffer media. As fibrils are very rich in β-sheet structure, a fibril sensor should be more specific toward the β-sheet structure so as to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 77 publications
1
30
1
Order By: Relevance
“…However, the in depth analysis of the binding to DNA can significantly contribute to shed light on the optical properties of ThT and their possible dependence on the hydrophobic local characteristics of the binding pocket. This information can be of use in the improvement of the biomedical/biological applications of ThT or similar sensors, whose optimisation represents a cutting‐edge research . Moreover, recent observations that ThT efficiently binds DNA aptamers, may open the way to novel sensing strategies where ThT acts as a signal reporter for DNA nanomechanical devices .…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, the in depth analysis of the binding to DNA can significantly contribute to shed light on the optical properties of ThT and their possible dependence on the hydrophobic local characteristics of the binding pocket. This information can be of use in the improvement of the biomedical/biological applications of ThT or similar sensors, whose optimisation represents a cutting‐edge research . Moreover, recent observations that ThT efficiently binds DNA aptamers, may open the way to novel sensing strategies where ThT acts as a signal reporter for DNA nanomechanical devices .…”
Section: Introductionsupporting
confidence: 71%
“…This information can be of use in the improvement of the biomedical/ biological applications of ThT or similar sensors, whose optimisation represents a cutting-edge research. [24,25] Moreover, recent observations that ThT efficiently binds DNA aptamers, may open the way to novel sensing strategies where ThT acts as a signal reporter for DNA nanomechanical devices. [22] Also, as recently shown by some of the present authors, ThT was found to bind natural DNA (double stranded B-helix conformation) with binding affinities on the order of 10 4 M 21 (T 5 258C, 0.01 M NaCl).…”
Section: Introductionmentioning
confidence: 99%
“…The a K value characterizing the AuO-BSAN binding also suggests the formation of fibrils of a certain morphology, differing from that observed by other authors. For instance, in the Mudliar's work BSA (100 µM) was incubated at 65 ºC for 2 hours resulting in the fibril formation and the a K value lower by 2 orders of magnitude compared to that obtained in the present study [32]. Interestingly, unlike lysozyme, BSAN and BSAF have similar number of the dye binding sites, supposedly with different morphology.…”
Section: Resultscontrasting
confidence: 40%
“…Interestingly, Mudliar et al reported AuO binding to the hydrophobic IIA domain of BSA, i.e. to the specific ligand-binding site [32,42]. These discrepancies could be due to the fact that Mudliar employed Auto Dock software, while the simple PatchDock/FireDock tools used in the present study give less precise results.…”
Section: Resultsmentioning
confidence: 58%
“…This binding model of ThT to amyloid fibrils is referred to as Channel binding model (Biancalana and Koide, 2010;Krebs et al, 2005). Thus, ThT interacts with a common structural feature of amyloid fibrils irrespective of protein type, be it Alzheimer's related fibrils (Maezawa et al, 2008) or prion associated amyloid fibrils (Sabate et al, 2008) or fibrils of generic protein like BSA (Mudliar et al, 2016). Importantly, ThT has been routinely employed in in vitro assays and kinetic studies of amyloid fibril formation, which not only gives insights into the molecular mechanism behind amyloid fibrillation process, but also aids in identifying potential inhibitors of protein fibrillation process.…”
Section: Thioflavin-t: Amyloid Fibril Sensormentioning
confidence: 99%